The Relationship Between Money Supply, Interest Rate and Inflation Rate: an Endogeneity-Exogeneity Approach - Kaplan, Fatih; Gungor, Sule (European Scientific Journal, ESJ, 2017)
After the 2008 Financial Crisis, The Central Bank is Turkey as well as many countries, has implemented a policy of increasing the money supply. It is a known fact that the changes in the money supply are considerable extent determinative in interest rate and inflation rate such as orientations of macro economics variables. The purpose of this study is to investigate the relationship between money supply, interest rate and inflation rate in Turkey after the 2008 Financial Crisis. In accordance with this purpose, 2008:1- 2015:12 period money supply, interest rate and inflation rate monthly data are used. Commonly in applied studies, the relationship between these variables is analysed with Cholesky Decomposition Method of Variance based Vector Autoregression Model (VAR). But this method is affected by ordering of the variables according to endogeneity-exogeneity approach, when ordering of the variables were changed, the results are changed and therefore policy proposals are changed. In analysis of the study, both Cholesky and Pesaran and Shin’s proposal method is used. According to Cholesky Variance Decomposition result at the end of the a month, when all changes in inflation is explained by inflation, this rate is 85% according to Generalized Decomposition Method of Variance result.